2017
DOI: 10.1007/s10482-017-0845-3
|View full text |Cite
|
Sign up to set email alerts
|

Massilia chloroacetimidivorans sp. nov., a chloroacetamide herbicide-degrading bacterium isolated from soil

Abstract: A Gram-stain negative, rod-shaped, aerobic bacterial strain, designated TA-C7e, was isolated from an agricultural soil obtained from Taean region, Korea. Phylogenetically, the strain was grouped with the genus Massilia and shared 95.33-97.97% 16S rRNA sequence similarity with the type strains of other species of the genus Massilia. The DNA-DNA hybridisation between TA-C7e and Massilia haematophila KACC 13771, Massilia suwonesis KACC 12635, and Massilia yuzhufengensis KACC 16569 revealed a low level of relatedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
(18 reference statements)
2
27
0
Order By: Relevance
“…The DNA G+C content of GEM5 T was 65.1 mol% (). This was close to the genome DNA G+C contents of other type strains of species in the genus Massilia [3, 11, 12, 29]. Therefore, these results indicated that GEM5 T represented a novel species of the genus Massilia .…”
Section: Genome Featuressupporting
confidence: 79%
“…The DNA G+C content of GEM5 T was 65.1 mol% (). This was close to the genome DNA G+C contents of other type strains of species in the genus Massilia [3, 11, 12, 29]. Therefore, these results indicated that GEM5 T represented a novel species of the genus Massilia .…”
Section: Genome Featuressupporting
confidence: 79%
“…Bacillus and Pseudarthrobacter significantly increased in salt-treated spermosphere soil groups compared with CS25 and CS20 via taxonomic analysis and qPCR assays (Figures 3 and 8). The two dominant bacteria genera in salt-treated spermosphere soil groups have previously been identified as common plant growth-promoting bacteria (PGPRs) [35][36][37][38]. Phosphorus is one of the essential mineral elements for plant growth, which is one of the major constituents in energy metabolism and biosynthesis of nucleic acids and cell membranes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Some members have propensity to produce bioactive substance such as dimethyl disulfide (DMDS), which could have potential for controlling plant foliar diseases 10 . In addition, M. chloroacetimidivorans has been reported to degrade chloroacetamide herbicide 22 . On the other hand, some species such as M. timonae , M. consociate , M. oculi and M. haematophila are considered as pathogenic strains as they were isolated from human clinical samples 7 , 8 , 18 .…”
Section: Introductionmentioning
confidence: 99%